The milky way - Daverio, Matteo; Tine', Mariaenrica; Spagnolo, Paolo (Monaldi Archives for Chest Disease, 2021)
Mediastinal masses may present with signs and symptoms due to either compression of mediastinal structures or systemic effects of the underlying disease. The present case highlights the advantages of interventional pulmonology in the diagnosis of lymphoma as a cause of chylothorax and superior vena cava syndrome.